0028 Using Simulation To Promote Safe And Therapeutic Services In Mental Health Settings. (1st November 2014) - Campbell, Lloyd; Reedy, Gabriel; Tritschler, Christina; Pathan, James; Wilson, Catherine; Jabur, Zainab; Luff, Adrian; Cross, Sean
Abstract : Background/context: Managing low-frequency, high-risk occurrences, such as psychiatric and physical deterioration is a challenge for any clinical service. It is even more so in mental health settings, where clinicians may have less experience with acute physical deterioration. Simulation is used for training in acute medical specialties, but is used relatively infrequently in mental health. 1 The Emergency Team Simulation course was designed to allow learners to explore their own and colleagues' practice, to recognise the impact of non-technical skills, to identify practical alternative behaviours and areas for improvement in providing safe and therapeutic mental health services. Method: The course was developed by simulation experts and mental health professionals and consisted of a multi-pilot, iterative design where feedback from each course contributed to the next pilot. Participants (n = 41 over five course days) were from multiple health professions across a large mental health trust who respond to emergency calls. The course consists of six scenarios, each followed by a structured debrief using the Diamond Debrief Model (Description, Analysis and Application). Scenarios include managing agitation, a patient in supervised confinement, escalating aggression, oversedation and a cardiac arrest. Results/outcomes: Participants completed anonymous feedback forms. Responses were generally positive, with all questions averaging above 4 on a 5-point Likert Scale. Over 97% of participants agreed the programme was useful and relevant to them, with 100% stating that they would recommend the course to a colleague. Most respondents identified specific lessons learned and changes they could apply to their own practice. Conclusion: Further research will be conducted on the course as it is rolled out on a larger scale, but these initial results indicate the potential for simulation to be a useful and valuable learning tool for managing acute situations in mental health settings. Reference: Dave S. Simulation in psychiatric teaching. Advances in Psychiatric Treatment 2012;18(4):292–298